Effect of natural and synthetic conditioners on soluble cations and water infiltration in an Aridisol - Henríquez, Manuel; Rodríguez, Orlando; Montero, Francisco; Hernández, Alexander (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the effect of several conditioners on soluble cations and water infiltration on a fine clay Vertic Haplocambid soil collected on the Quibor depression, Venezuela. Solutions of two natural conditioners from dato cactus (Lemaireocereus griceus (Haw.) Br. & Rose) and lefaria cactus (Cereus deficiens Otto & Dietr), on concentrations of 2,000, 1,000 and 500 mg L-1, a synthetic polyacrilamide conditioner solution of 10 mg L-1 and local tap water were applied to the soil. All solutions and the tap water were poured in a mini flume to simulate the irrigation process on furrows. The natural conditioners increased the infiltration and produced a better Ca-Mg-Na relationship as compared with that produced by the polyacrilamide and the tap water without additives.